فعالية تطبيق BOARDROOM في إدارة الصف لترقية مهارة الكلام لطلاب الفصل الثامن بالمدرسة المتوسطة الإسلامية الحكومية بيلانج كنتشنج ماديون - Rahmaningsih, Ulfa; Bakar, Yunus Abu; Wafa, Ali (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2019)
The teaching process that still uses traditional methods has an impact to students. One of that impact is the obstructed of student’s ability to master speaking skills, whereas the main function of language learning is as a communication tool. Therefore, researchers want to provide one way to improve the ability to speak Arabic, namely by using the Boardroom application. By using this application, the process of teaching Arabic in the classroom will be more innovative and raises student’s corage in their Arabic speaking skills. This research was conducted on eight grade students of the Belang Islamic junior high school, Kancheng Madiun. This study uses quantitative methods. The data collection process will be carried out by interviews, questionares, tests and drawings. Whit this method of data collection, the researchers will get more validity and depth data in the field.